Evolution of Fc Receptor-Like Scavenger in Mammals - Matos, Maria Carolina; Pinheiro, Ana; Melo-Ferreira, José; Davis, Randall S.; Esteves, Pedro José (Frontiers in Immunology, 2021)
Fc receptor-like (FCRL) molecules comprise a large family of receptors, homologous to the receptors for the Fc portion of immunoglobulins (FCR). Within this family, an unusual gene known to exist in mice, rats and dogs, termed FCRLS, encodes a chimeric protein with both Ig-like FCRL and type B scavenger-receptor cysteine-rich (SRCR)-like domains. In mice, FCRLS is located next to the CD5L and KIRREL1 genes. Here, we show that the curious FCRLS gene is actually present across major mammalian groups, but its annotation is generally incorrect or absent. Anchored on mouse FCRLS and FCRL2 genomic sequence alignments, phylogenetic analyses demonstrated that many mammalian sequences currently annotated as FCRL2 cluster with FCRLS, supported by a conserved genetic synteny among organisms. This analysis shows that FCRLS is present in Rodentia, some Carnivora (Canidae and Ursidae), Chiroptera, Arctiodactyla, Proboscidae and some Primata. Thus, the FCRLS most likely originated in a eutherian mammal ancestor since it is not present in Monotremata or Marsupialia. FCRLS has a peculiar distribution pattern across mammalian lineages, being present in some species, but absent in others from the same family, as in carnivores for example. The most parsimonious hypothesis to explain this FCRLS evolution is that it was convergently lost in several independent mammalian lineages. Analyses of branch-specific nucleotide evolutionary rates, show that FCRL2 and FCRLS have similar ranges of rates across mammals, suggesting that both genes have crucial, but separate functions in the immune system. Bayesian estimates of evolutionary rates for FCRLS in mammalian lineages revealed that carnivores display the highest mutation rate after rodents. Additionally, positive diversifying selection was detected for both FCRL2 and FCRLS. Our results show that the presence of the FCRLS gene is older and more widespread across mammals than previously thought and appears to be functional, being under positive selection. Its precise physiologic role should thus be investigated.